1993
DOI: 10.1016/0020-7292(93)90701-w
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of hormone receptors and proliferating cell nuclear antigen in aggressive angiomyxoma of the vulva

Abstract: We report on a case of AA as well as examine the literature to review a total of 32 cases. We note that AA is often misdiagnosed and tends to recur in the ischiorectal and retroperitoneal spaces. By means of immunohistochemical analysis, we conclude: the estrogen and progesterone receptor status was weakly positive, but could not be distinguished from the background-fibroblastic tissue, PCNA correlates well in this tumor with its low mitotic index; however, further similar studies are needed to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
3

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 10 publications
1
9
0
3
Order By: Relevance
“…3 In addition, other reports have demonstrated ER and/or PR positivity within aggressive angiomyxoma. [3][4][5][6][7] In our study, all five females patients showed positivity for ER, staining being weak or moderate in intensity. Four or five cases were strongly positive for PR throughout most of the tumour.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…3 In addition, other reports have demonstrated ER and/or PR positivity within aggressive angiomyxoma. [3][4][5][6][7] In our study, all five females patients showed positivity for ER, staining being weak or moderate in intensity. Four or five cases were strongly positive for PR throughout most of the tumour.…”
Section: Discussionsupporting
confidence: 54%
“…3 In addition, several reports have demonstrated oestrogen receptor (ER) and/or progesterone receptor (PR) positivity within this neoplasm, either by immunohistochemistry or by direct assay. [3][4][5][6][7] The aim of our study was to investigate the ER and PR status of six cases of aggressive angiomyxoma, including one in a male patient. We wished to determine whether this would be of value in the distinction between aggressive angiomyxoma and a variety of lesions that can mimic it.…”
mentioning
confidence: 99%
“…Immunohistochemistry staining for desmin, SMA, vimentin, CD34, S100 protein, and particularly for estrogen and progesterone receptors, is useful [9,10]. In our case, the estrogen and progesterone receptor statuses were positive, and S100 protein was negative, indicative of the typical features of AAM.…”
Section: Discussionmentioning
confidence: 57%
“…Some studies, however, have shown variable staining with desmin [7,9,10,13,14] and focal staining with smooth-muscle actin in a few cases (Table 3) [5,7,[10][11][12][13]. Similar to findings in aggressive angiomyxoma, positive estrogen and progesterone receptor studies have also been reported [13,[15][16][17]. One study demonstrated a few CD34 positive cases [10], whereas no reactivity was seen for this marker in a more recent report [13].…”
Section: Discussionmentioning
confidence: 89%
“…The immunohistochemical profile reported by Fletcher et al [1] indicated that there were sharp differences between these two tumors, but further studies have shown that the immunophenotype of the two tumors can be identical [1,10,13,14]. The matter is still not well defined, and although there are many similarities, the truth is that there are also many differences among them, including clinical and histologic differences (Table 4) [15][16][17][19][20][21][22][23][24][25][26][27][28]. The importance of distinguishing between the two lies in the clearly benign behavior of angiomyofibroblastoma, even when excision shows positive tumor margins.…”
Section: Discussionmentioning
confidence: 99%